Assessment of Food Safety Knowledge among School-Going Adolescents: An Interventional Study - Indumathi, S.; Sharma, Mahak; Sanghi, Divya (International Journal of Child Health and Nutrition, 2024)
Background: Recognizing the complex health issues that school-going adolescents face due to ignorance of proper food handling techniques, which impact their general development and severely threaten the health of both the present and future generations in all developing nations. This interventional study aimed to compare food safety knowledge among school-going teenagers (13–15 years) before and after intervention, taking into account the significance of students’ health importance in the early adolescent stages. Materials and Methods: The cluster sampling method was used to choose 400 students from four different schools. A food safety intervention education was given online using the Google Meet platform. The World Health Organization’s food safety questionnaire was used to gauge participant knowledge of food safety before and after the intervention. A committee of subject matter experts evaluated the research tool’s relevance for content validity. Results: Following the implementation of the intervention, significant increases in food safety knowledge were noticed among school-going adolescents in the post-test. A maximum of 81.5% of subjects gained a high-level knowledge regarding food safety after the food safety intervention. Statistics showed that the differences were substantial. After the intervention program, school-aged teenagers’ overall understanding of food safety dramatically increased. Conclusion: In order to reduce the health problems caused by unsafe food among school-going teenagers, awareness of food safety must be greatly raised through a variety of food safety training programs in the early stages of adolescence.